Optimum Level of Vessel Ligation in Splenic Flexure Cancer - Mahdi Hussain Al Bandar; Yoon Dae Han; Jamal Al Sabilah; Mohammed Al Suhaimi; Min Soo Cho; HyukHur; Byung Soh Min; Kang Young Lee; Nam Kyu Kim (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Aim: To investigate the level of vessel ligation in splenic flexure cancer (SFC) in term of oncology outcome and overall survival. Methods: From 2005 until 2012 records reviewed. 43 patients diagnosed with SFC enrolled and analyzed. Patients categorized based on the level of vessel ligation. Left branch of middle colic (LMA) and left colic artery division (LCA) compared to ligation of LCA and marginal of middle colic artery (MMC). Results: Twenty-four patients (55.8%) had LCA plus MMC, 19 patients (44.2%) approached at LCA plus LMA. Stage 1 rated at 25% in LCA plus MMC vs. 26.31% in LCA plus LMA, stage 2 and 3 found 33.4%, 4.2% vs. 42.1%, 31.57%, p=0.772, respectively. Harvested lymph nodes were similar, 19 ± 10 vs. 15 ±6.7, p=0.17, respectively. Recurrence rate found relatively greater in LCA plus MMC group compared to of LCA plus LMA but haven't reached statistical significant, 16.6% vs. 10.52%, p=0.56, respectively. 5-year disease-free survival and overall survival rate were similar in both groups. Conclusion: Higher level of vessel ligation has not add significant different in overall outcome, however, has a potential role to lower the risk of recurrence rate in SFC patients.